Inclusive Education and Social Inequality: An Anthropological Study of Social Mobility and Access to Education - Damyanov, Kaloyan (International Journal of Scientific Research and Management (IJSRM), 2024)
This research investigates the multifaceted relationship between inclusive education and social inequality, focusing on the potential of inclusive educational practices in Europe, with a specific case study in Bulgaria, to promote social mobility for marginalized populations. Grounded in an anthropological framework, the study seeks to understand how structural and cultural barriers impede access to equitable education for marginalized groups, with particular attention to Roma students, one of the most disadvantaged communities in Europe. By examining the educational landscape in Bulgaria, this research delves into the lived experiences of educators, psychologists, and occupational therapists working to implement inclusive education within a system often fraught with discrimination, limited resources, and institutional challenges.The qualitative research, conducted in Sofia from February to April 2024, draws on interviews, participant observation, and focus groups to capture the nuanced challenges and successes of those involved in delivering inclusive education. Findings reveal that despite national policies aimed at promoting inclusion, significant barriers persist, particularly for Roma students, who continue to face segregation, prejudice, and limited educational opportunities. Educators frequently report difficulties in accommodating the diverse needs of students within under-resourced schools, while psychological and cultural biases further hinder effective inclusion.Moreover, the study identifies a critical gap between policy and practice, where inclusive education policies are often poorly implemented due to a lack of cultural competence and institutional support. This gap has direct implications for the social mobility of marginalized students, as education remains a key determinant of their future opportunities. The findings underscore the urgent need for culturally responsive teaching strategies and support systems that are tailored to the unique socio-economic and cultural contexts of marginalized communities. These strategies must go beyond superficial inclusion to actively dismantle the entrenched inequalities that exist within educational institutions.This study emphasizes the pivotal role of inclusive education in addressing social inequality and promoting social mobility. However, it also highlights the significant work that remains to be done to ensure that inclusive education is truly accessible and effective for all, particularly for marginalized groups like the Roma. By proposing a series of culturally sensitive and contextually informed recommendations, the research advocates for a more holistic approach to inclusive education that can better support the academic and social advancement of marginalized students, ultimately fostering greater equity in educational outcomes and social mobility.